2022
DOI: 10.1007/s11356-021-17810-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-migraine activity of freeze-dried latex obtained from Calotropis gigantea Linn

Abstract: Migraine which is characterized by a pulsating headache affected an estimated population of 12% worldwide. Herbal products like latex derived from Calotropis gigantea R. Br. (Asclepiadaceae) are a representative intervention to treat migraine traditionally. However, post harvesting stability issues of latex affects its biological potential. Freeze drying has been successfully employed for the encapsulation of herbal bioactive compounds resulting in stable dried preparations. Latex derived from Calotropis gigan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The results of these studies demonstrated the reduction in immobility in the forced swimming test after acute pre-treatment at 125 mg/kg, and after 14 days of treatment at 30 and 125 mg/kg [66,67]. Moreover, the latex extracted from the aerial parts of C. gigantea decreased apomorphine-induced climbing behaviour, l-5-HTP-induced syndrome, and MK-801-induced hyperactivity in a dosedependent way by influencing dopaminergic and serotonergic receptor interaction [65].…”
Section: In Vivo Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…The results of these studies demonstrated the reduction in immobility in the forced swimming test after acute pre-treatment at 125 mg/kg, and after 14 days of treatment at 30 and 125 mg/kg [66,67]. Moreover, the latex extracted from the aerial parts of C. gigantea decreased apomorphine-induced climbing behaviour, l-5-HTP-induced syndrome, and MK-801-induced hyperactivity in a dosedependent way by influencing dopaminergic and serotonergic receptor interaction [65].…”
Section: In Vivo Studiesmentioning
confidence: 89%
“…The most used plant parts are leaves, like S. europaea, A. officinalis, P. major, while N. tangutorum was the only one testing the fruit [32,[68][69][70]. Further, several methods were used for extracting the biomass, including drying samples under sunlight, freezedrying microencapsulated latex for C. gigantea [65], refluxing for 1 h in aqueous ethanol for A. venetum leaves [66,67], and using hot distilled water at 60 • C for 15 min for P. major leaves [70]. Additionally, 95% ethanol was used for 3 h with stirring for N. tangutorum fruit [69], and enzyme-digested PhytoMeal ethanol extract (PM-EE) was used for S. europaea stem and leaves [32].…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation